STUDENT EXPECTATIONS AND CHOICE OF THE AREA OF STUDY AT THE NATIONAL INSTITUTE OF YOUTH, PHYSICAL EDUCATION, AND SPORT (INJEPS) OF THE UNIVERSITY OF ABOMEY CALAVI (UAC) - ASSOGBA, Anicet Paterne Coovi; EDOH, KOFFI PIERROT; BIGA, BOKARY ALASSANE; DOUKA SOUMAÏLA, Aboubacar (My University, 2019)
The present research proposes to show that the choice of a study department by a student depends on the expectations he / she has for that training pathway. That choice, which is in relation with the student's aptitudes, also is, with the training offers (Job opportunities) after graduation. Three hundred and eighty-four (384) students (293 enrolled in STAPS and 91 in STASE) were selected from the 862 regularly enrolled for the academic year 2017-2018 (658 in STAPS and 204 in STASE). At the end of the data collections and the various statistical analysis, it appears that more students choose the STAPS department to solve the questions of professional insertions which constitute a priority issue for them. Those who move to the STASE department are less numerous because the job offers are less important in that sector. Thus, job applications are less favourably answered than in the first department. However when they end up being hired, their working conditions and rewards are usually more interesting. Beyond the profile which also influences the university orientation, the student who enrols in INJEPS chooses the STAPS department if his priority is to find a job quickly. But he moves to the STASE department, if he prefers to take the time to look for a job that matches his social status and the standing that goes with it.
Keywords: Students; expectations; Orientation; Study departments; Training; and job opportunities.